Patients with Helicobacter Pylori Infections Who Have Iron Deficiency Anemia (IDA) - M Abdullah, Mounis Ahmad Zaffar, Syed Hassan Musanna, Sheraz Saleem, Javaria Amil, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: It is the goal of this research to evaluate the presence of iron deficiency anaemia (IDA) in individuals with Helicobacter pylori infection. Study Design: Prospective/cross-sectional study Place and Duration: Department of medicine, Ittefaq Hospital Trust, Lahore, during the period from 16th January 2021 to 15th July 2021. Methods: There were one hundred and thirty patients of both genders with ages 22-60 years were presented. Informed written consent was taken from all the patients included age, sex, body mass index, education status and residency. All the included patients had helicobacter pylori infection in this study. Blood samples from the individuals were tested for serum iron, transferrin saturation, ferritin, and total iron-binding capacity. A urea breath test, stool antigen testing, a quick urease test, or histopathology may all be used to look for H. pylori infection. SPSS 22.0 version was used to analyze complete data. Mean standard deviation was used for laboratory outcomes. Results: Mean age of the patients 35.32 ± 6.53 years with mean BMI 26.12±8.64 kg/m2. Majority of the patients were females 75 (57.7%) and remaining were males 55 (42.3%). 53 (40.8%) patients were from urban areas and 60 (46.2%) patients were literate. Most of the patients 80 (61.5%) had poor socio-economic status. Mean Hemoglobin level was 11.12 ± 1.8 (g/dl) mean serum iron level was 50.3 ± 12.45 (ug/dl) and mean serum ferritin level was 123.4±56.55 (ng per ml).We found iron deficiency anemia in 51 (39.2%) patients. Conclusion: Iron deficiency anaemia was shown to be more prevalent in individuals with Helicobacter Pylori infection who were mostly females in this research.